Caracterização das nascentes e ecossistemas dependentes das águas subterrâneas: estudo de caso no município de Analândia-SP - Luiz, Junio da Silva (Universidade Federal de São Carlos, 2019)
The analysis of springs by models to geomorphological aspects and by studies of Groundwater Dependent Ecosystems (GDEs) are good tools to manage water resources. However, there is a lack of information, both on the classification of springs and on the GDEs. The objective of this work is to provide subsidies to increase the understanding about the themes. For this, a field study was carried out in the city of Analândia-SP, and from 28 springs several aspects were addressed regarding the classification of springs and the GDEs, using the models already available in the literature and trying to understand the relationship with the springs found in the field. Springs were found that fit 06 geomorphological models of springs and a range of information related to GDEs. It was possible, from the results, to see that the models adopted and the GDEs compression can be two useful tools for decision making.
Caracterizacion of springs and groundwater dependent ecosystems: case study in the city of Analândia-SP
Keywords: Nascentes; Ecossistemas dependentes de águas subterrâneas; GDE; Recursos hídricos; Gestão de recursos hídricos; Groundwater dependent ecosystems; Water resources and management; Springs; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA::GEOLOGIA AMBIENTAL; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA::HIDROGEOLOGIA; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::AGUAS SUBTERRANEAS E POCOS PROFUNDOS; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::PLANEJAMENTO INTEGRADO DOS RECURSOS HIDRICOS